EFFICIENCY ANALYSIS OF GOLD PAWN IN ISLAMIC COMMERCIAL BANKS IN INDONESIA - Abdullah Haidar; Nur Hendrasto; Evania Herindar (The Pontianak State Institute of Islamic Studies, 2023)
The purpose of this study is to examine the efficiency of the Islamic banking business in Indonesia, specially Islamic Rural Bank in Central Javas. As a component of Indonesia's Islamic banking ecosystem, it is critical to understand the extent those banks work optimally together to support the development of Islamic finance, particularly during the Covid-19 pandemic, and to realize public welfare, particularly through productive financing consistent with Sustainable Development Goals Objectives. In the periode ofÂ 2016 until 2020, this study examined a sample ofÂ 20 Islamic Rural Banks in central Java. The study was conducted using a non-parametric approach known as DEA (Data Envelopment Analysis). The intermediation strategy was used to determine the input and output variables in this study. Fixed assets, operational costs, and third-party money are included as input variables. Meanwhile, the output variable is made up of the quantity of finance granted and the amount of operating income earned. The findings of this study reveal that the efficiency of Islamic Rural Bank in Central Java has a shifting tendency across the 2016â€“2020 timeframe, with the average bank experiencing a decline in efficiency during the COVID-19 pandemic. Additionally, this study assesses the possibility for improvement of inefficient programs using input and output data. The primary source of inefficiency is in the output variable, particularly in terms of customer financing. Additionally, this research makes recommendations to a variety of stakeholders, including practitioners, academics, and regulators.